Brine Shrimp Lethality Activity of Thai Medicinal Plants in the Family Meliaceae - Pisutthanan, Sirintorn; Plianbangchang, Pinyupa; Pisutthanan, Nisit; Ruanruay, Siriluk; Muanrit, Onrudee (Asian Health, Science and Technology Reports, 2004)
Brine shrimp larvae have been used as a bioassay for a variety of toxic substances. The method has also been applied to plant extracts in order to facilitate the isolation of biologically active compounds. In this study, the plants in the family Meliaceae have been selected to test for brine shrimp lethality activity based on taxonomic approach including Azedirachta indica, Azedirachta indica var. siamensis, Melia azedarach, Sandoricum indicum and Swietenia macrophylla. The stem bark and leaf were separately collected and investigated for their activities. All of the stem bark extracts, except S. macrophylla, showed significant toxicity whereas all of the leaf extracts were inactive. The stem bark of Annona squamosa, which exhibited brine shrimp toxicity, has been used as positive control and its leaf and seed were also examined. The result showed that the leaf and seed of this plant exhibited higher potency than the stem bark.